2016
DOI: 10.5194/acp-16-10543-2016
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of urban fluxes of methane, carbon monoxide and carbon dioxide above London, UK

Abstract: Abstract. We report on more than 3 years of measurements of fluxes of methane (CH4), carbon monoxide (CO) and carbon dioxide (CO2) taken by eddy-covariance in central London, UK. Mean annual emissions of CO2 in the period 2012–2014 (39.1 ± 2.4 ktons km−2 yr−1) and CO (89 ± 16 tons km−2 yr−1) were consistent (within 1 and 5 % respectively) with values from the London Atmospheric Emissions Inventory, but measured CH4 emissions (72 ± 3 tons km−2 yr−1) were over two-fold larger than the inventory value. Seasonal v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 38 publications
5
62
0
Order By: Relevance
“…The seasonality of methane emissions caused by variation of the source strength is supported by the study of methane fluxes in central London by Helfter et al . 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The seasonality of methane emissions caused by variation of the source strength is supported by the study of methane fluxes in central London by Helfter et al . 7 .…”
Section: Discussionmentioning
confidence: 99%
“…However, while many specific approaches have been developed for the estimate of total methane fluxes (e.g. refs 37), there is no established methodology that leads to a comprehensive partitioning of emissions by sources. Tracer methods based on Fourier Transform Infrared (FTIR) absorption spectroscopy 8 , flux chambers 9 and mobile ground surveys 10 are all used for the estimation of total emissions from a specific source area (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Higher built-up density could be directly associated with a large NG distribution pipeline, NG consumption, and high vehicular traffic (Sarak and Satman, 2003). In particular, Helfter et al (2016) showed that the differences in built-up density within the flux footprint explained up to 90% of the spatial variability of the annual CH 4 fluxes.…”
Section: Spatial Variations Of Atmospheric Methane Concentrationmentioning
confidence: 97%
“…Each possible CH 4 source in the study site has a characteristic temporal emission. The mean atmospheric CH 4 concentration in an urban site results from an overlap between sources with either constant or time-varying emission rates (Helfter et al, 2016). A clear differentiation of sites and the influence of the different sources may be masked by seasonal variation, and, therefore, a further detailed temporal analysis is necessary.…”
Section: Spatial Variations Of Atmospheric Methane Concentrationmentioning
confidence: 99%
See 1 more Smart Citation